The Effectiveness of QAR Strategy in Improving Junior High School Learners’ Reading Comprehension: A Lesson of Deep Reading Processes - Tiara, Uci; Mertosono, Sudarkam R.; Lebagi, Desrin; Marhum, Mochtar (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
Reading comprehension is a crucial skill for students, yet many face challenges due to limited vocabulary and ineffective reading strategies. This study investigates the effectiveness of the Question-Answer Relationship (QAR) strategy in enhancing reading comprehension among eighth-grade students at SMP Negeri 15 Sigi. Utilizing a quasi-experimental design, the research involved an experimental group receiving QAR-based instruction and a control group following conventional methods. Data were gathered through pre-tests and post-tests and analyzed using SPSS version 22. The results revealed that the experimental group achieved a significantly higher post-test mean score (69.57) compared to the control group (58.83), with an independent sample t-test value of 0.018 (p < 0.05). These findings confirm that the QAR strategy effectively improves reading comprehension by assisting students in categorizing and responding to questions more accurately. The strategy not only enhances comprehension but also fosters critical thinking and increases student engagement during reading activities. Consequently, teachers are encouraged to incorporate the QAR strategy into their reading instruction to promote deeper understanding and improve academic outcomes. By integrating QAR, educators can support students in developing more effective reading strategies, ultimately leading to improved literacy skills and learning success.